Local Wisdom Molaulita Integrates Character Education Management: Kearifan Lokal Molaulita dalam Manajemen Pendidikan Karakter - Ananya, Nurhayati Oktavia; Gagaramusu, Yusdin Bin. M.; Rahmawati, Dyah; Rizal, Rizal; Guci, Ammar Abdullah Joni (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the implementation of local wisdom-based character education management through the “Molaulita” culture at an elementary school. General Background: Character education is essential for developing intellectually capable, morally grounded, and culturally rooted students. Specific Background: Integrating local wisdom into school activities offers a contextual approach to strengthen character formation and cultural identity. Knowledge Gap: Previous practices often lack systematic management and fail to consistently integrate local wisdom into structured educational programs. Aims: This study aims to describe the “Molaulita” culture and analyze its management in supporting character education at SD GKST Peura. Results: Findings show that “Molaulita,” implemented through weekly co-curricular storytelling in the Poso (Pamona) language, functions as both cultural preservation and a medium for character development, fostering communicative skills, responsibility, patriotism, and curiosity. The program is managed through planning, organizing, actuating, controlling, and evaluating, involving school leaders, teachers, and students. Novelty: The study provides an empirical model of character education management grounded in local culture through structured co-curricular activities. Implications: The findings highlight the potential of integrating local wisdom into educational management to support sustainable character development and cultural preservation in elementary education. Highlights:• Weekly storytelling activities embed cultural language use in classroom practice• Management functions structure co-curricular programs for character formation• Student traits develop through routine participation and guided reflection Keywords: Education Management; Character Education; Local Wisdom; Molaulita; Elementary School